SEX DETERMINATION BY ADN IN FIVE MACAW SPECIES - Liza R., Jacqueline (2008)
Determination of sex in wild birds is crucial in developing conservation plans for threatened species. The absence of sexual dimorphism in birds makes impossible to determine sex based on physical characteristics and sexing has traditionally depended upon surgical methods which are highly stressful for the animals. The present study had the purpose of developing of a noninvasive DNA test for sex determination in macaws (guacamayos). Blood samples from five species (Ara ararauna, Ara chloroptera, Ara macao, Ara militaris y Propyrrhura couloni) were studied. DNA was extracted and specific primers were used to amplify both exons and introns of the chd (chromo-helicase- DNA-binding) gene located on the sex chromosomes of all birds. Females are identified by chd-ZW on the W chromosome and males by chd-ZZ on the Z chromosome. The amplification was carried out by the optimization of the conditions and the PCR cycles. Two fragments of 300-400 bp were detected in female birds and one in males. Sex determined by conventional methods in 31 birds agreed with DNA results. The molecular test was also used to sex 28 macaws of unknown sex, including 11 Propyrrhura couloni.